SEBUTAN DAN SAPAAN DALAM ISTILAH KEKERABATAN BAHASA TONTEMBOAN SUATU KAJ IAN LINGUISTIK ANTROPOLOGI - Stelnie H. Perutu (Balai Bahasa Sulawesi Utara, 2011)
The research about naming and addressing in Tontemboan Language Kinship Terminology is necessary and still relevant nowadays due to a lot of supporting factors for the language resistance such as attitude and appreciation which are about to be forgotten by the Minahasans. In fact, the director of Kawan Pustaka ( 2004.130) said that “the culture identity.... is respected along with the changing of the time and civilization